2008
DOI: 10.1093/aje/kwn318
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk After Exposure to Treatments for Ovulation Induction

Abstract: Uncertainty continues as to whether treatments for ovulation induction are associated with increased risk of cancer. The authors conducted a long-term population-based historical cohort study of parous women. A total of 15,030 women in the Jerusalem Perinatal Study who gave birth in 1974-1976 participated in a postpartum survey. Cancer incidence through 2004 was analyzed using Cox's proportional hazards models, controlling for age and other covariates. Women who used drugs to induce ovulation (n = 567) had inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 45 publications
4
103
0
2
Order By: Relevance
“…In contrast, some earlier case series and epidemiological studies (Whittemore et al, 1992;Rossing et al, 1994;Shushan et al, 1996) reported positive associations, with risk being particularly high in the subgroup of nulligravid women, whereas among those who took drugs but did achieve a pregnancy the risk was not significantly different from that among gravid women without a history of infertility. More recent cohort (Modan et al, 1998;Venn et al, 1999;Klip et al, 2002;Doyle et al, 2002;Brinton et al, 2004;Calderon-Margalit et al, 2008;Jensen et al, 2009) and case -control (Ness et al, 2003) studies, however, have failed to find any such association. The lack of clear trends with time since start of treatment would also argue against the hypothesis that ovulation stimulation induces growth of pre-existing latent tumours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, some earlier case series and epidemiological studies (Whittemore et al, 1992;Rossing et al, 1994;Shushan et al, 1996) reported positive associations, with risk being particularly high in the subgroup of nulligravid women, whereas among those who took drugs but did achieve a pregnancy the risk was not significantly different from that among gravid women without a history of infertility. More recent cohort (Modan et al, 1998;Venn et al, 1999;Klip et al, 2002;Doyle et al, 2002;Brinton et al, 2004;Calderon-Margalit et al, 2008;Jensen et al, 2009) and case -control (Ness et al, 2003) studies, however, have failed to find any such association. The lack of clear trends with time since start of treatment would also argue against the hypothesis that ovulation stimulation induces growth of pre-existing latent tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined this question but three large cohort studies reported increases among women exposed to high doses or with longer follow-up (Modan et al, 1998;Althuis et al, 2005;Calderon-Margalit et al, 2008). Such a link would be biologically credible as clomiphene and tamoxifen are both selective estrogen-receptor modulators and tamoxifen use has been shown to be associated with an increased risk of cancer of the uterus (Swerdlow et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then an increased amount of FSH stimulates development of follicles, ultimately resulting in ovulation (Randal and Templeton 1991;Martikainen et al 2006;Chaman and Asmatullah 2011). Some authors have reported that treatment with clomiphene is related with various malignancies including endometrial and ovarian cancers (Derman and Adashi 1994;Althuis et al 2005;Lerner-Geva et al 2006;Calderon-Margalit et al 2009;Jensen et al 2009). …”
Section: Clomiphenementioning
confidence: 99%
“…I tabell 1 vises data og konklusjoner fra publikasjoner som omhandler risiko for brystkreft etter infertilitetsbehandling. Flere rapporter konkluderer med at det ikke er økt risiko for brystkreft etter infertilitetsbehandling (6)(7)(8)(9)(10)(11)(12)(13). I noen studier konkluderes det med en redusert risiko for brystkreft etter behandling for infertilitet (14,15).…”
Section: Risiko For Brystkreftunclassified